2021
DOI: 10.3389/fimmu.2021.650427
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of CD4 Cytotoxic T Cells in High-Risk Neuroblastoma

Abstract: Neuroblastoma is the most common extracranial childhood solid tumor. The majority of high-risk neuroblastoma is resistant/refractory to the current high intensity therapy, and the survival of these patients remains poor for the last three decades. To effectively treat these extremely unfavorable neuroblastomas, innovative immunotherapy approaches would be the most promising. In this article, we discuss the identity of tumor-infiltrating effector cells and immunosuppressive cells in high-risk neuroblastoma. Neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 98 publications
1
22
0
Order By: Relevance
“…We previously reported that macrophages were predominant PD-L1+ cells in neuroblastoma tissues at diagnosis based on multiplex IHC analysis [ 5 ]. In this report, we further extended this observation by examining the prognostic effect of PD-L1 expression in two large neuroblastoma gene expression datasets, including SEQC-498 (Cohort 1) and Kocak-649 (Cohort 2) [ 30 , 31 ] (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that macrophages were predominant PD-L1+ cells in neuroblastoma tissues at diagnosis based on multiplex IHC analysis [ 5 ]. In this report, we further extended this observation by examining the prognostic effect of PD-L1 expression in two large neuroblastoma gene expression datasets, including SEQC-498 (Cohort 1) and Kocak-649 (Cohort 2) [ 30 , 31 ] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CD8 CTLs are thus expected to play little role in the anti-neuroblastoma immune response. Our previous study suggests that CD4 CTLs are important effector cells against high-risk neuroblastoma, but the CD4 CTL mediated-“protective effect” declines over time, in part due to the progressive formation of an immunosuppressive tumor microenvironment (TME) [ 5 ] and/or chemotherapy-induced suppression of hematopoiesis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether these cells exacerbate, or counter tumour progression or metastasis formation remains to be fully elucidated and might depend on the tumour type and/or stage. Recently, CD4 T cells displaying a cytotoxic gene signature were reported in children with high-risk neuroblastoma and were associated with a putative protective effect that declined over time due to the progressive formation of an immunosuppressive tumour microenvironment ( 74 ). CD4 CTLs were also observed in B-cell chronic lymphocytic leukaemia (B-CLL), where they were able to kill autologous B-CLL cells ex vivo in a perforin-mediated mechanism ( 75 , 76 ).…”
Section: Cd4 Ctls In Pathologic Conditionsmentioning
confidence: 99%
“…Our group and others have shown that there are different subtypes of TMEs found in neuroblastoma and that the TME of pediatric neuroblastoma is not only associated but plays an active role in the clinical outcomes of these patients [ 10 , 12 , 50 , 51 ]. A variety of therapeutic approaches to harness a patient’s immune system to target the tumor have been developed.…”
Section: Introductionmentioning
confidence: 99%